Cardiovascular safety risks associated with gout treatments. Issue 9 (1st September 2020) - Rosas, Giovanna; Gaffo, Angelo; Rahn, Elizabeth J.; Saag, Kenneth G.
ABSTRACT: Introduction: Uric acid is the final byproduct of purine metabolism. The loss of the enzyme that hydrolyzes uric acid to allantoin was lost, leading to a decrease in uric acid excretion and its further accumulation. The buildup of uric acid leads to damage in different organ systems, including the cardiovascular system. With the increasing burden of cardiovascular disease worldwide, a growing body of evidence has addressed the relationship between urate, cardiovascular outcomes, and gout medication cardiovascular safety. Areas covered: We discuss the most common gout therapies used for the reduction of serum urate and management of gout flares in different observational and clinical trials and their effects on different aspects of cardiovascular disease. We selected the most representative clinical studies that evaluated cardiovascular outcomes with each gout therapy as well as recommendation given by the most representative guidelines from Rheumatology societies for the management of gout. Expert opinion: The treatment of gout reduces joint damage and it can also lessen CV morbidity. Allopurinol shows CV safety profile when compared to other ULTs. Evidence supporting CV safety with the use of colchicine and IL-1 agents is promising and research needs to be conducted to further assess this outcome.